2014
DOI: 10.1159/000366306
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Gintonin-Mediated Membrane Depolarization of Pacemaker Activity in Cultured Interstitial Cells of Cajal

Abstract: Background/Aims: Ginseng regulates gastrointestinal (GI) motor activity but the underlying components and molecular mechanisms are unknown. We investigated the effect of gintonin, a novel ginseng-derived G protein-coupled lysophosphatidic acid (LPA) receptor ligand, on the pacemaker activity of the interstitial cells of Cajal (ICC) in murine small intestine and GI motility. Materials and Methods: Enzymatic digestion was used to dissociate ICC from mouse small intestines. The whole-cell patch-clamp configuratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 696 publications
(17 citation statements)
references
References 66 publications
(104 reference statements)
0
17
0
Order By: Relevance
“…In a previous study, we found that ANO1 was well expressed in ICCs within 12 hours of culture, but subsequently decreased with time [40]. Therefore, in the present study, we used ICCs that had been cultured for least than 12 hours (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In a previous study, we found that ANO1 was well expressed in ICCs within 12 hours of culture, but subsequently decreased with time [40]. Therefore, in the present study, we used ICCs that had been cultured for least than 12 hours (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, TRPM7 and ANO1 mRNA have been reported in ICCs and TRPM7 and ANO1 currents have been described [24,35,40,41]. Thus, we examined the effects of quercetin on the expressions of ANO1 and TRPM7 channels in HEK 293 cells, which overexpress both channels.…”
Section: Involvements Of Ano1 and Trpm7 Channels During Pacemaker Actmentioning
confidence: 99%
See 1 more Smart Citation
“…Slow waves play an important role in the regulation of GI motility by determining the frequency and timing of smooth muscle contractions, and ICCs, which are connected to smooth muscle cells by gap junctions to form a network, are the pacemaker cells that generate slow waves by producing spontaneous PPs. Accordingly, PPs generated by ICCs are directly transmitted to smooth muscles through gap junctions [13][14][15]. In addition, ICCs mediate inhibitory and excitatory signals from the enteric nervous system to smooth muscles, and thus, importantly regulate GI motility.…”
Section: Discussionmentioning
confidence: 99%
“…It has been determined that Poncirus fructus (PF) is able to modulate pacemaker electrical potentials via the 5-hydroxytryptamine (5-HT) 3 and 5-HT 4 receptor pathways in a MAPK-dependent manner (24) and gintonin-mediated membrane depolarization and Ca 2+ -activated Cl -channel activation have been observed in cultured murine ICCs via a lysophosphatidic acid 1/3 receptor signaling pathway (41). Additionally, it was determined that San-Huang-Xie-Xin-tang (SHXXT) is able to modulate pacemaker electrical potentials (42).…”
Section: Discussionmentioning
confidence: 99%